Utilização de cabo guarda extra para melhoria de desempenho de linhas de transmissão - Alexandre Marmelo dos Passos Junior (2010)
Overvoltages in transmission lines originated from lightning are objects of big concern in companies and utilities involved with transmission and distribution of electric energy. In most cases, failures in the transmission and distribution systems of large industrial parks generate long production interruptions, equipments failures, raw material and pre-finished products losses, characterizing huge financial losses. These and other factors, as the cost of electric energy in the final product, make this input a strategic factor in the management of industrial processes, as well as strategic throughout the installation of generation and transmission of electric power in large industrial parks. Thus, managing the operational risk of a power system in large industrial parks, with respect to transmission and distribution, involve studies and investments for improving the performance of transmission lines.In this context, this work aims to present the use of EGW Extra Ground Wire as an alternative to improve the performance of transmission lines, comparing it to conventional alternatives.This work is developed by simulations in the PSCAD software, where are imulated flashes in a 69kV transmission line, for backflashover simulations. To build the set of data for analysis, the simulations are done for different values of relevant parameters on the overhead transmission lines performance: front time current wave, footing tower resistance value and span length. These same simulations are performed for a transmission line with similar characteristics, however, using EGW positioned at different locations under phase conductors.From these data, a statistical analysis is applied to determine the comparative performance between the EGW transmission line and the conventional transmission line Further studies are performed simulating changes in footing resistance and insulation level of the transmission line, in order to reach the same performance improvement achieved with EGW providing an overall comparison of three alternatives